Increased NOD1, but not NOD2, activity in subcutaneous adipose tissue from patients with metabolic syndrome - Zhou, Yi‐Jun; Liu, Cong; Li, Chun‐Li; Song, Yu‐Ling; Tang, Yin‐Si; Zhou, Hui; Li, Ai; Li, Yan; Weng, Yang; Zheng, Fang‐Ping (Obesity (Silver Spring, Md.), 2015)
Objective Nucleotide‐binding oligomerization domain (NOD) protein, as cytoplasmic receptor of the innate immune response, plays an important role in adipose inflammation and insulin resistance in obesity. Our objective was to examine adipose tissue (AT) NOD in nascent metabolic syndrome (MetS) patients and to investigate its association with MetS features. Methods Thirty‐four MetS subjects and 31 controls were recruited. Fasting blood was collected, and abdominal subcutaneous AT was obtained by biopsy for NOD1/NOD2 expression and activity. Results MetS subjects showed significantly increased expression for NOD1 on adipose depots as compared to controls. In addition to increased expression of downstream signaling mediators RIPK2 and NF‐κB p65 nuclear translocation, there was remarkably higher release of monocyte chemotactic protein1 (MCP‐1), interleukin (IL)‐6, and IL‐8 in MetS versus controls following priming of the isolated adipocytes with NOD1 ligand iE‐DAP. With regard to NOD2, the differences between the two groups were not significant in either basal state or after activation. Increased NOD1 positively correlated with waist circumference. NOD1 was also correlated with HbA1c and HOMA‐IR. NOD1 positively correlated with serum levels of IL‐6, MCP‐1, and NF‐κB activity. Conclusions Activation of the innate immune pathway via NOD1 may be partially responsible for the increased systemic inflammation and insulin resistance in MetS.